Pengaruh Strategi Komunikasi terhadap Kinerja Individu dan Kepuasan Kerja (Studi pada Kepolisian Resort Malang Kota) - Sapoetra, Yudistira Arya; Surachman, .; Susilowati, Christin (Universitas Brawijaya, Indonesia, 2013)
This study aims to reveal the effect of communication strategy is built as a medium for deliver messages between superiors to subordinates. This study reveals the influence of the communication strategy adopted in the performance of the police against individuals, as well as its effect on job satisfaction of police officers. Sample size was 85 respondents as members of the police district of Malang city. Data retrieved using direct survey method with a questionnaire instrument to be further analyzed in two stages. The first phase of the data was analyzed using confirmatory factor analysis to determine the factor scores of each indicator, and hereinafter PLS analysis which is the second stage of data analysis to test the research hypothesis. Study findings in the form of empirical evidence of the positive influence on job satisfaction communications strategy that communication strategies in the police managed to increase job satisfaction. Also found to influence the performance of individual communication strategy. While job satisfaction among variables does not affect the performance of the individual.